The Effectiveness of Rice Straw and Cogongrass Straw Soaked Water Attractants on the Number of Aedes spp. Mosquitoes - Alprian Wiratama; Zairinayati - (Poltekkes Kemenkes Surabaya, 2026)
Aedes spp. mosquitoes are the main vectors of Dengue Hemorrhagic Fever (DHF), which remains a public health problem in Indonesia. Chemical insecticide-based mosquito control has the potential to cause environmental pollution and vector resistance, so safer and more environmentally friendly control alternatives are needed. This study aimed to analyze the effectiveness of rice straw and cogongrass straw-soaked water attractants in attracting Aedes spp. mosquitoes. Method this study used a pure experimental design with a post-test only control group design. The study was conducted at Muhammadiyah Ahmad Dahlan University, Palembang. Traps were placed purposively with a total of 27 observation units consisting of three treatment groups, namely control (water without attractant), rice straw-soaked water attractant, and cogongrass straw-soaked water attractant, each with nine replications. Traps were set for 5–7 days. Data were analyzed using the Shapiro–Wilk normality test, homogeneity test, One Way ANOVA, and the Least Significant Difference (LSD) test with a significance level of 0.05. The results showed the total number of mosquitoes trapped in the control group was 16, in the rice straw attractant group was 31, and in the cogongrass straw attractant group was 32. The average number of mosquitoes in the control group was 2.00 ± 0.67, in the rice straw group was 3.00 ± 1.13, and in the cogongrass straw group was 4.00 ± 1.13. The results of the One- Way ANOVAanalysis showed a significant difference between the treatment groups (p = 0.01). Further LSD tests showed that both attractant groups were significantly different from the control, but there was no significant difference between the rice straw and cogongrass straw attractants. These findings indicate soaked water from rice straw and cogongrass straw was effective in increasing the number of trapped mosquitoes compared to the controlas a natural attractant to catch Aedes spp. mosquitoes and has the potential to be an alternative vector control that is cheap, easy to apply, and environmentally friendly.